An unexpected discovery of a new species in Alloclavaria (Rickenellaceae, Hymenochaetales) from China - Deng, Peng-Tao; Yan, Jun; Liu, Xiang-Fen; Zhang, Ping (Phytotaxa, 2023)
A newly discovered fungal species associated with conifers in China, Alloclavaria orientalis, is formally described and illustrated. A molecular phylogenetic analysis of concatenated internal transcribed spacer and nuclear ribosomal RNA large subunit sequences supported the monophyly of A. orientalis as a distinct lineage within the Alloclavaria clade.